STUDI AKSESIBILITAS OBJEK WISATA BUMI ALMIRA - Citra Artifiani Havianto; Rita Leswati; Firdha Amelia Sundawa (GEOPLANART, 2022)
Kabupaten Bandung Barat is one of the Kabupaten in West Java which is famous for its natural tourism. One of the developing tourist objects in Kabupaten Bandung Barat is Bumi Almira. An important factor that influences tourists visiting a tourist attraction is accessibility to that tourist attraction. This research aims to study the accessibility of Bumi Almira Tourism Objects. This research method is descriptive quantitative. The sampling technique used is accidental sampling with 30 tourists as respondents. The research variables used are alternative roads, road conditions, travel distance, travel time, availability of public transportation and the cost of visiting tourist attraction. Data analysis used a scoring technique with the Struges formula. The results of the study show that accessibility to Bumi Almira Tourism Objects is in the very supportive category.